Biodegradable polymer biolimus-eluting stent versus durable polymer everolimus-eluting stent in patients with acute myocardial infarction. (15th March 2015) - Lee, Hyun Jong; Park, Taek Kyu; Song, Young Bin; Choi, Young Jin; Yu, Cheol Woong; Yang, Jeong Hoon; Hahn, Joo-Yong; Choi, Seung-Hyuk; Choi, Rak Kyeong; Choi, Jin-Ho; Park, Jin Sik; Kim, Je Sang; et al.
Abstract: Background: There are limited data about long-term outcomes for biodegradable polymer biolimus-eluting stent (BES) versus durable polymer everolimus-eluting stent (EES) in patients undergoing percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI). We sought to compare the two-year efficacy and safety of BES versus EES in AMI patients. Methods: A total of 707 consecutive patients with ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction who underwent PCI with BES (n = 171) or EES (n = 536) between July 2008 and June 2012 were enrolled in this study. The efficacy endpoint (target vessel failure; a composite of cardiac death, target vessel-related myocardial infarction, and target vessel revascularization) and the safety endpoint (a composite of all cause death, myocardial infarction, and stent thrombosis) at two years were compared in crude and propensity score-matched cohorts. Results: After two years, target vessel failure occurred in 13 patients treated with BES and 49 patients treated with EES (7.6% versus 9.1%; adjusted hazard ratio [HR], 1.09; 95% confidence interval [CI], 0.58–2.04; p = 0.78). The rates of composite safety endpoint at two years were not different between two groups (BES 7.6% versus EES 10.8%; adjusted HR, 0.87; 95% CI, 0.47–1.62; p = 0.66). The rates of stent thrombosis did not differ between two groups (BES 0.6% versus EES 1.3%; adjusted HR, 0.63; 95% CI, 0.06–6.20; p = 0.69). These findings were substantiated by similar results in the propensity score-matched cohort. Conclusions: In the treatment of patients with AMI, BES showed similar efficacy and safety compared to those of EES for up to two years. Highlights: We compare the two-year efficacy and safety of BES versus EES in AMI patients. The two-year efficacy of BES is similar to that of EES in AMI patients. The two-year safety of BES is similar to that of EES in AMI patients. The rate of probable or definite stent thrombosis was low and comparable between two groups.